2016
DOI: 10.1103/physrevb.94.014435
|View full text |Cite
|
Sign up to set email alerts
|

Band structure and spin texture ofBi2Se3 3dferromagnetic metal interface

Abstract: The spin-helical surface states in three-dimensional topological insulator (TI), such as Bi2Se3, are predicted to have superior efficiency in converting charge current into spin polarization. This property is said to be responsible for the giant spin-orbit torques observed in ferromagnetic metal/TI structures. In this work, using first-principles and model tight-binding calculations, we investigate the interface between the topological insulator Bi2Se3 and 3d-transition ferromagnetic metals Ni and Co. We find … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
63
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(65 citation statements)
references
References 40 publications
2
63
0
Order By: Relevance
“…These limitations suggest that the coupling between the magnetic material and the TI surface [29,49], as well as the contribution of bulk states [69] …”
Section: Discussionmentioning
confidence: 99%
“…These limitations suggest that the coupling between the magnetic material and the TI surface [29,49], as well as the contribution of bulk states [69] …”
Section: Discussionmentioning
confidence: 99%
“…Interface (a) (considered in Ref. 7) gives a lower energy than interface (b) by 0.07 eV upon the relaxation. Therefore, henceforth, we present results obtained from interface (a).…”
Section: The Descendent State At the Interface From The Lattice mentioning
confidence: 99%
“…In the cases of TIinsulator bilayers, first-principles studies have found that interface states localized a bit deeper into the interface appear near the Fermi level E F with Dirac-like dispersion, while the original Dirac surface states are shifted way below E F due to band-bending potentials, which are induced by the mismatch between chemical potentials [8][9][10][11] . As for TI-metal heterostructures, effective model studies have found Dirac interface states becoming diffusive under weak TI-metal coupling 12 while first-principles studies have reported no spin-momentumlocked interface states for various metals 7,13 . In particular, severe hybridization is expected for cases where electrons in the Dirac interface states are coupled to many itinerant electrons with similar momenta and energies from a metal slab with much higher chemical potential.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the surface states are altered by the Fermi level shift, band bending, and possible creation of additional surface states. It has been shown that the spin-momentum locked surface states could be completely destroyed by a magnetic overlayer [13]. However our simplifying model is most useful in addressing the most recent experimental results in which the predominant contribution to spin-charge conversion can be attributed to Dirac cone 2D states.…”
Section: Introductionmentioning
confidence: 99%